The translation of an Italian procura alle liti into English: word-by-word rendering or functional translation? - Patrizia Giampieri (Comparative Legilinguistics, 2023)
Ad hoc corpora are considered effective to deliver native-like technical (and legal) translation. This paper explores how the translation of a system-specific document such as an Italian procura alle liti (power of attorney to appear in court) can be addressed. Translating this legal document may be problematic due to the fact that it is not recurrent in the common law system, which contemplates other types of special powers of attorney (PoAs). This paper explores whether and to what extent a corpus-based translation is possible when L2 parallel texts are difficult to find in native contexts. To this aim, a translation project with technical translators and lawyers is carried out. The participants compose an ad hoc corpus which they consult as a language reference tool. The paper findings report that the translators' corpus-based translation is mostly a word-by-word rendering of the source text, which may sound unnatural to an expert of the field. The lawyers' translation partly deviates from source words, but addresses the communicative function of the source text. The paper highlights the need for a balance between the two strategies, for example by focusing on textual functionality and/or paraphrasing, although at the cost of a reduced formulaicity.